Paleonestrain and paleodirection of the geomagnetic field during the Cretaceous superchron and in the Paleocene by rocks of West Antarctica - V. V. Scherbakova; V. G. Bakhmutov; V. P. Scherbakov; G. V. Zhidkov; V. V. Shpira; Z. I. Smirnova; Ye. S. Sergienko (Ukrainian Antarctic Journal, 2009)
The complex palaeomagnetic research of a representative collection of Andean Intrusive Suite from the western part of Antarctic Peninsula (near Ukrainian Antarctic base Academik Vernadsky) were carried out. The collection of samples is various on a chemical compound and includes gabbrous, diorites and quartz diorites, tonalities, granodiorites and granites. The age of igneous complex varies from 58 to 106 Ma, most of the rocks to date from Upper Cretaceous (Cretaceous magnetic polarity subchron). The magnetic and petromagnetic parameters of samples have been studied in two laboratories. The palaeomagnetic directions have been calculated after whole temperature demagnetization. For palaeointensity determination the significant part of a collection using Thellier-Coe method with “checkpoints” procedure have been studied. For six points authentic definitions of palaeointensity are received. Seven from 8 VDM values are twice or more times below its present day value. Average value VDM in Cretaceous is 5.7х1022 Am2, at high scope of secular variations VDM changes from 1.1x1022 Am2 to 14x1022 Am2. By comparison of average values VDM in Cretaceous subchron and Paleocene show the close values which confirm the hypothesis about absence of correlation between VDM values and inversions frequency.